Beyond Job Resources: Integrating Islamic Human Resource Management into the Job Demands-Resources Model to Mitigate Teacher Burnout - Siskha Putri Sayekti; Isep Djuanda; Eva Siti Faridah; Winda Nidya Putri Fitriana; Eda Laelasari (JURNAL AL-TANZIM, 2026)
This study systematically synthesizes empirical evidence regarding the role of Islamic Human Resource Management (IHRM) in preventing teacher burnout amidst digital transformation. The research employs a Systematic Literature Review (SLR) method based on PRISMA 2020 guidelines. A literature search across eight electronic databases covering the period 2015–2025 yielded 212 articles, with 17 studies meeting the inclusion criteria. Methodological quality was assessed using the JBI Checklist and CASP Qualitative Checklist, while data were synthesized through thematic analysis using a narrative synthesis approach. The findings identify five key dimensions of IHRM: Islamic-value-based recruitment and selection, spirituality-integrated professional development, Islamic leadership that serves and empowers, fair compensation and rewards, and work-life balance. These practices prevent burnout through three interconnected mechanisms: spiritual-emotional resources, social support, and competence-empowerment. In the context of digital education, IHRM strengthens teacher resilience by framing technology as a meaningful work tool, reinforcing organizational support, and fostering solidarity based on ukhuwah (Islamic brotherhood). This study extends the Job Demands–Resources model by positioning spiritual resources as a protective factor against teacher burnout.